Practical Management of Thyroid Cancer A Multidisciplinary Approach - Mazzaferri, Ernest L.; Harmer, Clive; Mallick, Ujjal K.; Kendall-Taylor, Pat (Springer London : Imprint: Springer, 2006)
Practical Management of Thyroid Cancer follows the American and European model of treating thyroid cancer according to the high standards recommended by the available guidelines. All rare and curable cancers including thyroid cancers with a good prognosis should be treated by a multidisciplinary team of experts following published guidelines. This essential volume is therefore directed not only to the management of thyroid cancer in developed countries but is also the model that will be highly attractive to the developing countries. This is an invaluable reference to health care professionals, from primary to tertiary care, involved in the management of thyroid cancer such as clinical nurse specialists, clinical psychologists, family medicine practitioners, specialists in palliative care (especially for anaplastic thyroid cancers), genetics as well as surgeons, endocrinologists, oncologists, pathologists, and radiologists.